Is There Really a Sex Recession? Period and Cohort Effects on Sexual Inactivity Among American Men, 2006–2019. Issue 6 (November 2021) - Bozick, Robert
There has been a growing concern among researchers and media commentators that men in the United States may be increasingly less sexually active, creating a form of a "sex recession." Using 14 years of survey data from men in the National Survey of Family Growth (2006–2019), this study assesses whether such concerns are warranted. Cross-classified mixed-effects models are estimated to ascertain whether there is evidence of a population-wide sex recession among men due to secular conditions specific to different time periods, or if birth cohorts that comprise the male population at any given point in time are exhibiting distinct patterns of sexual behavior. The analysis finds no evidence of a population-wide sex recession among men. Rates of sexual inactivity among men have been constant across the time series, but those born between 2000 and 2004 had significantly higher rates of sexual inactivity than previous birth cohorts did at the same age. Additionally, men who are unemployed and/or living at home with their parents are more likely to refrain from sexual intercourse than their peers who are employed and/or living independently of their parents.